The relationship between work environment stress and marital happiness among software professionals - Priyadarshini Srinivasan, * (Sunway University College, 2010)
The aim of this research paper is to examine the relationship between marital happiness, profession and work environment. The participants in this research consist of 130 adults (65 software professionals and 65 non-software professionals) who are married and working. The age range was from 25-55 years old with a mean age of 38.49 years. In this study there were 73 (56.2%) male participants, 57 (43.8%) female participants. A survey method was used in this study and participants were required to complete the Dyadic Adjustment Scale (DAS) and Employee survey. This study found that there is a significant relationship between work environment, profession and marital happiness, thus proving all hypotheses proposed in this study. The study found that software professionals experience more work environment stress and less marital happiness compared to non-software professionals.